Asymmetric warming among elevations may homogenize plant α-diversity and aboveground net primary production of alpine grasslands - Han, Fusong; Yu, Chengqun; Fu, Gang (Frontiers in Ecology and Evolution, 2023)
It is well known that asymmetric warming among elevations (i.e., warming magnitude increases with increasing elevation) will weaken the difference of air temperature among elevations. However, it remains controversial on whether asymmetric warming among eleva-tions can homogenize plant α-diversity and above-ground net primary production (ANPP) in alpine regions. In the present study, we conducted an experiment of asymmetric warming among elevations in alpine grasslands, Northern Tibet since 2010. There were four experiment treatments, including a treatment under natural conditions at elevation 4313 m (C4313), a treatment under natural conditions at elevation 4513 m (C4513), a treatment under warming conditions at elevation 4513 m (W4513) and a treatment under warming conditions at elevation 4693 m (W4693). We investigated ANPP, taxonomic α-diversity (i.e., species richness, Shannon, Simpson and Pielou) and phylogenetic α-diversity (mean nearest taxon distance, MNTD; phylogenetic diversity, PD) in 2011–2019. There were no significant differences of mean air temperature between C4313 and W4513, or between C4513 and W4693 in 2011–2019, indicating the differences of air temperature were eliminated among elevations. Then we found that the differences of plant α-diversity and ANPP were also eliminated among elevations: (1) There were no significant differences of ANPP, Pielou and MNTD between C4313 and W4513, or between C4513 and W4693 in 2011–2019. (2) There were also no significant differences of mean species richness, Shannon and Simpson between C4513 and W4693 in 2011–2019. (3) There were also no significant differences of ANPP, species richness, Shannon, Simpson, Pielou, PD and MNTD between C4313 and W4513, or C4513 and W4693 in 2019. Therefore, asymmetric warming among elevations may homogenize plant α-diversity and aboveground net primary production in alpine grasslands, at least in Northern Tibet.